From Midwifery to Birth Assistance: Midwives’ Practice in the First Half of the 20th Century in the Czech Lands - Hana Stoklasová (Theatrum Historiae)
The paper deals with midwives’ practice in the first half of the 20th century. The issue is based on the analysis of serial sources, so-called birth diaries. The research analyses ten series of birth diaries in the pre-printed form in which the midwives recorded information on the course of deliveries. The diaries are kept in Czech and Moravian archives and provide data on obstetric practice in various regions of the Czech lands. That makes it possible for us to compare the circumstances under which the midwives worked as well as their performance in different geographical, demographic, and social conditions, both in industrial and agrarian areas. The obtained data provide answers to several questions, e.g. the beginnings of assistants’ careers, their performance, the social structure of their clientele, as well as medical aspects of obstetric practice and cooperation with physicians. The research attempts to define the links between these indicators and also focuses on the financial gains of the midwives in their obstetric practice.